Implementation of Fantasy Gymnastics to Develop Physical Health in Children Aged 5-6 Years at Islamic Kindergarten Bakti 63 Tanjung Harapan - Windari, Ratna; Isnaini, Isnaini; Andre, Lesis; Mirdad , Jamal (The Future of Education Journal, 2025)
This research is motivated by the importance of developing physical health in early childhood as a foundation for optimal physical and motor growth. Children aged 5–6 years are in a golden period of development, thus requiring proper stimulation through fun and age-appropriate physical activities. The research problem is: How is the implementation of fantasy gymnastics to develop physical health in children aged 5–6 years at TK Islam Bakti 63 Tanjung Harapan? The study aims to determine how the implementation of fantasy gymnastics can develop the physical health of children aged 5–6 years. This research employs a qualitative approach with a descriptive method. The respondents consisted of 15 students from group B, two kindergarten teachers, and several parents. The research was conducted in March–April 2025, using observation, interviews, and documentation for data collection. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Data validity regarding the implementation of fantasy gymnastics to develop physical health in children aged 5–6 years was ensured through data triangulation. The results show that the implementation of fantasy gymnastics at TK Islam Bakti 63 Tanjung Harapan ran well and suited the characteristics of active and imaginative 5–6-year-old children. This activity effectively influenced the development of physical health by encouraging children to be more active and confident, while improving gross motor skills, stamina, and movement coordination. Observations revealed that 12 children showed improvement in gross motor skills, 13 participated actively, and 12 demonstrated better fitness and healthy lifestyle habits. Fantasy gymnastics not only impacted physical skills but also fostered healthy lifestyle patterns and active participation, making it a fun and beneficial learning strategy for developing early childhood physical health. The study concludes that implementing fantasy gymnastics regularly and creatively at TK Islam Bakti 63 Tanjung Harapan is effective in developing the physical health of children aged 5–6 years.